Effectiveness of Alcohol, Smoking, and Substance Involvement Screening Test-Linked Brief Intervention on Harmful and Hazardous Alcohol Use in Nigerian Semirural Communities: A Non-Randomized Intervention Study - Lasebikan, Victor (Front Psychiatry, 2017)
OBJECTIVE: To determine the prevalence of alcohol consumption and the effectiveness of the alcohol, smoking, and substance involvement screening test (ASSIST)-linked brief intervention on hazardous and harmful alcohol use in semirural settings in Nigeria. METHODS: In this single arm non-randomized intervention study delivered by community health extension workers (CHEW), participants (N = 1,203), 15 years and older, recruited between October 2010 and April 2011 were assessed for prevalence of alcohol consumption and the associated level of risk. Scores of 0–10 were classified as lower risk scores, 11–26 as moderate risk, and 27+ as high risk. This was followed by a brief intervention. Prevalence of alcohol consumption and level of risk was assessed at 3 and 6 months postbrief intervention. Main outcome measure was the change in ASSIST scores at 3 and 6 months postintervention. RESULTS: There was a statistically significant difference in the prevalence of alcohol use at baseline compared with that at 6 months, χ(2)(2) = 4.2, p = 0.01. Among all respondents, a repeated measures ANOVA with a Greenhouse–Geisser correction showed that mean ASSIST score significantly reduced between time points [F(1.541, 34.092) = 53.241, p < 0.001]. Post hoc tests using the Bonferroni correction revealed that this difference was due to a significant reduction in the mean ASSIST scores at 3 months vs. baseline, p = 0.001, but not at 3 vs. 6 months, p = 0.09. CONCLUSION: There is a potential for CHEW-administered ASSIST-linked screening, brief intervention, and referral to treatment for unhealthy alcohol use in Nigerian semirural communities. This is feasible considering serious dearth of addiction specialists in the country.